Novel Zirconia Surface Treatments for Enhanced Osseointegration: Laboratory Characterization - Ola H. Ewais; Fayza Al Abbassy; Mona M. Ghoneim; Moustafa N. Aboushelib (Hindawi Limited, 2014)
Purpose. The aim of this study was to evaluate three novel surface treatments intended to improve osseointegration of zirconia implants: selective infiltration etching treatment (SIE), fusion sputtering (FS), and low pressure particle abrasion (LPPA). The effects of surface treatments on roughness, topography, hardness, and porosity of implants were also assessed. Materials and Methods. 45 zirconia discs (19 mm in diameter × 3 mm in thickness) received 3 different surface treatments: selective infiltration etching, low pressure particle abrasion with 30 µm alumina, and fusion sputtering while nontreated surface served as control. Surface roughness was evaluated quantitatively using profilometery, porosity was evaluated using mercury prosimetry, and Vickers microhardness was used to assess surface hardness. Surface topography was analyzed using scanning and atomic force microscopy (α=0.05). Results. There were significant differences between all groups regarding surface roughness (F=1678, P<0.001), porosity (F=3278, P<0.001), and hardness (F=1106.158, P<0.001). Scanning and atomic force microscopy revealed a nanoporous surface characteristic of SIE, and FS resulted in the creation of surface microbeads, while LPPA resulted in limited abrasion of the surface. Conclusion. Within the limitations of the study, changes in surface characteristics and topography of zirconia implants have been observed after different surface treatment approaches. Thus possibilities for enhanced osseointegration could be additionally offered.